A paradoxical dynamic in a service labyrinth: insights from HIV care. (12th November 2018) - Cruz, Angela Gracia B.; Snuggs, Elizabeth; Tsarenko, Yelena
Abstract : Purpose: While theories of complex service systems have advanced important insights about integrated care, less attention has been paid to social dynamics in systems with finite resources. This paper aims to uncover a paradoxical social dynamic undermining the objective of integrated care within an HIV care service system. Design/methodology/approach: Grounded in a hermeneutic analysis of depth interviews with 26 people living with HIV/AIDS (PLWHA) and drawing onBourdieu's (1984) theory of capital consumption to unpack dynamics of power, struggle and contestation, the authors introduce the concept of the service labyrinth. Findings: To competently navigate the service labyrinth of HIV care, consumers adopt capital consumption practices. Paradoxically, these practices enhance empowerment at the individual level but contribute to the fragmentation of the HIV care labyrinth at the system level, ultimately undermining integrated care. Research limitations/implications: This study enhances understanding of integrated care in three ways. First, the metaphor of the service labyrinth can be used to better understand complex care-related service systems. Second, as consumers of care enact capital consumption practices, the authors demonstrate how they do not merely experience but actively shape the care system. Third, fragmentation is expectedly part of the human dynamics in complex service systems. Thus, the authors discuss its implications. Further research should investigate whether a similar paradox undermines integrated care in better resourced systems, acute care systems and systems embedded in other cultural contexts. Originality/value: Contrasted to provider-centric views of service systems, this study explicates a customer-centric view from the perspective of heterosexual PLWHA.